Tradisi Mangitak pada Masyarakat Batak Angkola di Kabupaten Padang Lawas Utara - Abdul Amin Siregar (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
In this study the focus of the problem is the Mangitak Tradition in the Angkola Batak Community in North Padang Lawas Regency. This study aims to find out the history and dynamics of the Mangitak Tradition in the Angkola Batak Community in North Padang Lawas Regency. This study used historical research methods through four stages, namely heruistic, verification, interpretation, and histography, using three data collection techniques, namely observation, interviews, and documentation. Data collection techniques were carried out by visiting research locations such as North Padang Lawas Regency. The results obtained in this study are the history of the mangitak tradition and the changes that have occurred in the Mangitak Tradition in the Angkola Batak Community in North Padang Lawas Regency, where the background of the Mangitak tradition is the remains of ancestors passed down to the Angkola Batak community in North Padang Lawas district who experienced changes due to the progress of time. The Mangitak Tradition in the Angkola Batak Community in North Padang Lawas Regency has a very deep philosophy which is about a harmonious family.